Assessment of the forecast of the operating mode of the complex of ammonia secondary condensation production in uncertainty conditions - Babichenko, Anatolii; Kravchenko, Yana; Babichenko, Juliya; Velma, Volodymyr; German, Eduard (Premier Publishing s.r.o., 2020)
The article describes the analysis of conditions of secondary condensation complex functioning. There, the software algorithm for estimating the forecasts of functioning mode is developed, which makes it possible to prepare the complex operator in conditions of existing uncertainty for making decisions in supervisor control mode.
Keywords: secondary condensation; ammonia production; forecast evaluation; uncertainty conditions